Implementation of Word Square Learning Model in Vocabulary Learning (adjectives and nouns) Japanese Language in 11th Grade Students at YADIKA High School, Langowan District - Sandra Rakian (Journal of International Conference Proceedings (JICP), 2020)
Teacher Deployment Program Activities in Schools (PDS) are very beneficial for the lecturers and the school as well as LPTK. The Teacher Deployment Program in Schools (PDS) has a symbiotic nature of mutualism, meaning that it benefits both parties, both the school and the Lecturer and LPTK. An innovative learning model that can encourage students' understanding of Japanese vocabulary mastery. One form of innovative learning models is the Word Square learning model. Word Square learning model can be used to encourage students 'understanding of the subject matter, can train students' discipline, can train their attitudes carefully and critically and can stimulate students to think effectively. Of the 20 students who were tested in the pre-test before applying the Word Squared learning model in studying Japanese vocabulary can be seen from the results of the average grade of 49.5. Whereas after using the Word Square learning model, the progress of learning outcomes is so well evidenced by the average grade of the post-test that reaches 90.15. This proves that the application of the Word Square learning model in learning Japanese vocabulary plays a big role in a teaching and learning system, especially for education.